Filantropi Islam: Kinerja Badan Amil Zakat Nasional (BAZNAS) Pasca Pandemi Covid-19 - Ayulyn Nisail Musyarofah; Fiora Nur Oktivania; Agus Eko Sujianto (Universitas 45 Surabaya, 2023)
This article discusses the performance of the National Amil Zakat Agency (BAZNAS) during the post-Covid-19 pandemic in 2019-2021. Islam has advocated philanthropic activities to solve problems in society such as poverty. One of the philanthropic activities is zakat. Indonesia itself has an official institution that collects and manages zakat nationally, namely the National Zakat Amil Agency (BAZNAS). The existence of the Covid-19 pandemic has had an impact on all lines of life, including BAZNAS. The formulation of the problem in this research is regarding the performance of BAZNAS after the Covid-19 pandemic in 2019-2021. The type of research used in this research is quantitative research with a descriptive research approach. The sample used is the 2019-2021 BAZNAS financial reports. The performance measurement method used is the International Zakat Management Standard (ISZM) which consists of efficiency and capacity components. Based on this research, it was found that BAZNAS' performance was not good during the Covid-19 pandemic but after the Covid-19 pandemic, BAZNAS performance improved.